On positive approximations of positive diffusions - Mackevičius, Vigirdas (Lietuvos matematikos rinkinys, 2007)
For positive diffusions, we construct split-step second-order weak approximations preserving the positivity property. For illustration, we apply the construction to some popular stochastic differential equations such as Verhulst, CIR, and CKLS equations.